Analisis IT Service Management Pada Aplikasi Traveloka Menggunakan Framework ITIL V3 - Jennifer Arjun; Fenny Lestari; Tata Sutabri (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Information technology nowadays is developing very rapidly, especially in the tourism sector. The use of technology in the tourism sector has made Traveloka's services popular because they can be accessed easily, quickly and reliably. The Traveloka service provides a service where users can order plane tickets from various airlines that collaborate with Traveloka with different price variants. This service makes it easier for people to enjoy their holidays and find out plane ticket prices easily. This research used data collection through questionnaires and obtained 30 respondents. Then a validity and reliability test is carried out to measure the quality level of a statement, after which a maturity level calculation will be carried out to analyze whether Traveloka's services are good enough to carry out service operations in the community. This research uses the ITIL V3 framework to analyze Traveloka services, especially in the Service Operation domain, which consists of 5 subdomains, namely the maturity level in the Event Management subdomain gets a value of 4.41, the maturity level in the Incident Management subdomain gets a value of 4.22, then for the Problem subdomain Management got a maturity level of 4.17, then for the Request Fulfillment subdomain the maturity level got a value of 4.21 and finally for the Access Management subdomain it got a maturity level of 4.30. So it can be seen that based on the results of the maturity level calculation it can be stated that all subdomains are at the Managed Level.